2022
DOI: 10.7759/cureus.32547
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Sanitary Latrines and the Practice of Open-Air Defecation in a Rural Setup in Perambalur District: A Cross-Sectional Study

Abstract: BackgroundPublic health initiatives aim to decrease infectious diseases by enhancing sanitation, which is their primary goal. The practice of sporadically contaminating the environment with human feces has been around for generations and is embedded in the cultural behavior of villagers in India. This study aimed to estimate the proportion of people with access to latrine facilities and the proportion of people who practice open defecation in the villages of Perambalur, Tamil Nadu. MethodologyThis community-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This study observed that many caregivers often disposed child's faecal matter in an open environment-a practice that most likely increases the risk of contamination that results to diarrhea in children (Mulatya & Ochieng, 2020). Other works also observed that many (5.6 million) Kenyans as well as other populations still practice open defecation (Busienei et al, 2019;Tamilarasan et al, 2022;Water and Sanitation Program, 2012). This means that open defecation is still an issue that needs to be dealt with especially in the Low-and Middle-Income Countries (LMIC).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This study observed that many caregivers often disposed child's faecal matter in an open environment-a practice that most likely increases the risk of contamination that results to diarrhea in children (Mulatya & Ochieng, 2020). Other works also observed that many (5.6 million) Kenyans as well as other populations still practice open defecation (Busienei et al, 2019;Tamilarasan et al, 2022;Water and Sanitation Program, 2012). This means that open defecation is still an issue that needs to be dealt with especially in the Low-and Middle-Income Countries (LMIC).…”
Section: Discussionmentioning
confidence: 66%
“…An analysis of the Kenya demographic Health Survey 2014 showed that low level of caregiver education and unsafe disposal of children feces as key risk factors for diarrhea (Mulatya & Ochieng, 2020). Furthermore, providing health education to community members despite their level of education helps in making conscious decisions to avoid open defecation (Tamilarasan et al, 2022). According to a study conducted in India, open defecation was often practiced because of challenges in putting up latrines and the availability of land (Tamilarasan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation